"The familiar face of a word": Wittgenstein and Benjamin on the experience of meaning. (26th March 2018) - Stern, Alexander
Abstract: In what is now called Philosophy of Psychology—A Fragment (formerly Part II of the Philosophical Investigations ), Wittgenstein writes that the importance of the concept of aspect‐seeing "lies in the connection between the concepts of seeing an aspect and of experiencing the meaning of a word." Wittgenstein claims that just as we can imagine someone who does not experience shifts between two aspects in the same image—for example, the duck–rabbit—we can imagine people who use language but do not experience the meaning of a word. In this paper, I explicate the importance of this "meaning‐blindness" and its relation to aspect‐seeing. I then argue—drawing on a similar thought experiment in Walter Benjamin's early philosophy of language—that meaning‐blindness is actually a fatal impediment for language use. The upshot of my analysis is that the aesthetic experience of meaning, regularly marginalized in the philosophy of language, must be understood as fundamental to language and language use.